Iowa RBA, December 13-17, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Six emails of Iowa RBA updates for December 13-17, 1999. Highlights of the updates include sightings of a Yellow-billed Loon, Lesser Black-backed Gull, Thayer's Gull, Snowy Owl, White-winged Crossbill, Black Scoter, and a Long-tailed Duck. Epson - sheet feed/flatbed